Herbivorous fishes : - Opuszynski, Karol (CRC Press, 1995)
This exciting new book focuses on freshwater, rather than marine, herbivorous fishes, primarily Chinese carp. Herbivorous fishes are important not only as food fish, but also as a means for biological vegetation control. Fish were placed into the herbivorous category if they consumed greater than fifty percent plant material. Fish herbivory, including feeding methods, digestive processes, and energy relationships, is covered in detail. Culture, use for food, aquatic weed management, and effects on the environment are also discussed.